2019
DOI: 10.17531/ein.2019.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Welding tendency for selected contact materials under different switching conditions

Abstract: Welding tendency for selected contact materials under different sWitching conditions Tendencja sczepiania wybranych maTeriałów sTykowych w różnych warunkach łączeniowychThe flow of significant current through electric contacts may lead to contact welding. In a.c. circuits this phenomena is not only dependent on properties of contact material (i.e. resistance to welding) but on the phase in which current is switched on. Welding tendency for contact materials made from AgNi, AgCdO and AgSnO 2 was evaluated based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…As AgNi and AgCdO are less resistant to contact welding, the phenomenon occurred in them and the contact made of AgSnO 2 and AgSnO 2 P remained resistant. Studies have shown [25] that contact welding occurs only when the switching phase is π/2 and a bounce occurs. However, some materials, like AgSnO 2 and AgSnO 2 P, are immune to contact welding at this current level, as compared to AgNi and AgCdO.…”
Section: Resultsmentioning
confidence: 99%
“…As AgNi and AgCdO are less resistant to contact welding, the phenomenon occurred in them and the contact made of AgSnO 2 and AgSnO 2 P remained resistant. Studies have shown [25] that contact welding occurs only when the switching phase is π/2 and a bounce occurs. However, some materials, like AgSnO 2 and AgSnO 2 P, are immune to contact welding at this current level, as compared to AgNi and AgCdO.…”
Section: Resultsmentioning
confidence: 99%
“…Relevant to the welding strength is the load current and the duration of the bounce. The strength of the weld increases with the amplitude of the applied current [4]. As bouncing events become shorter with each subsequent bounce an increase in the weld strength for late bounce events, somewhat growing exponentially past the 4 th bounce can be observed [75].…”
Section: ) Contact Weldingmentioning
confidence: 99%
“…The EMR is a versatile component found in many electrical systems e.g., consumer products or safety critical applications in the nuclear-or aviation industry. Over several decades, EMR failure modes and mechanisms in particular relating to electrical contact degradation have been subject of extensive studies [1], in order to improve design and material properties [2]- [4].…”
Section: Introductionmentioning
confidence: 99%
“…In electromagnetic relays, the flow of current of a considerable value can lead to the emergence of an electrodynamic force, affecting the contact system, and it can be large enough to cause a dynamic opening of the contacts. As a result, an electric arc will occur between the contacts, which may be welded [1][2][3][4] when the contacts close again. Welded contact will make the relay inoperable, which will necessitate its replacement or an exchange of the entire device within which it is incorporated.…”
Section: Introductionmentioning
confidence: 99%
“…There are studies that utilize the contact force to describe the working principles of electrical equipment [16]. Many studies combine electrodynamic bounce of contacts with contact welding [1][2][3]. As shown in these studies there is a relation between contact bounce, contact welding, and electrodynamic force, however they do not focus on that subject.…”
Section: Introductionmentioning
confidence: 99%